Protection of the right to information on one’s health – a non-jurisdictional form of protection - Khodieieva, N. V.; Ходєєва, Н. В.; Yasynok, M.; Kuryliuk, Y.; Filippov, S.; Zemko, A.; Yasynok, D. (International Journal of Criminology and Sociology. – 2021. – № 10. – Р. 630-635, 2021)
У статті аналізуються теоретичні аспекти захисту суб'єктивних цивільних прав та визначаються рамки цивільно-правових відносин щодо інформації про своє здоров'я. Отримано більш чіткий та повний опис особливостей реалізації права на інформацію про своє здоров'я у нормативно встановленій системі захисту суб'єктивних прав людини. Встановлено, що захист права на інформацію про своє здоров'я здійснюється вільно, і невикористання особою права на захист не є підставою для припинення цього права. Зазначається, що при захисті свого порушеного права на медичну інформацію уповноважена особа може вчиняти певні дії, не пов'язані зі зверненням до компетентних державних органів та є неюрисдикційною формою захисту. Систематизовано перелік дій фізичної особи щодо захисту права на інформацію про своє здоров'я за неюрисдикційної форми захисту зазначеного права.

The article analyzes the theoretical aspects of protection as directly subjective civil rights and defines them within the framework of civil relations regarding the information on one's health. A clearer and complete description of the features of the realization of the right to information on one's health in the normatively established system of protection of subjective rights of a person has been obtained. It has been determined that the protection of the right to information on one's health is exercised freely, and the failure of a person to exercise the right to protection is not a ground for termination of this right. It is noted that during the protection of their violated right to health information, the authorized person may perform certain actions that are not related to the appeal to the competent state bodies and are a non-jurisdictional form of protection. The list of actions of an individual to protect the right to information on one’s health in the case of a non-jurisdictional form of protection of the above-mentioned right has been systematized.

В статье анализируются теоретические аспекты защиты субъективных гражданских прав и определяются рамки гражданско-правовых отношений по поводу информации о своем здоровье. Получено более четкое и полное описание особенностей реализации права на информацию о своем здоровье в нормативно установленной системе защиты субъективных прав человека. Установлено, что защита права на информацию о своем здоровье осуществляется свободно, и неиспользование лицом права на защиту не является основанием для прекращения этого права. Отмечается, что при защите своего нарушенного права на медицинскую информацию уполномоченное лицо может совершать определенные действия, не связанные с обращением в компетентные государственные органы и являющиеся неюрисдикционной формой защиты. Систематизирован перечень действий физического лица по защите права на информацию о своем здоровье при неюрисдикционной форме защиты указанного права.
Keywords: право на інформацію; стан здоров'я; захист суб'єктивних цивільних прав; right to information; state of health; protection of subjective civil rights; право на информацию; состояние здоровья; защита субъективных гражданских прав